2019
DOI: 10.3390/sym12010053
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Interface: User Interface of Asymmetric Virtual Reality for New Presence and Experience

Abstract: This study proposes an asymmetric interface that can provide head-mounted display (HMD) and non-HMD users with improved presence and an experience consistent with the user’s environment in an asymmetric virtual reality. For the proposed asymmetric interface, a controller-based hand interface is designed for portability, easy and convenient use, and high immersion. Subsequently, a three-step decision-making structure that supports accurate and efficient decision-making is defined based on the asymmetric experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…These game designs can leverage the benefits of multiplayer game experiences (e.g., supporting social connectedness; Woods, 2009;Vella et al, 2019) without requiring additional HMDs. Examples include giving bystanders insight into the virtual environments (VEs) inhabited by the HMD player (e.g., via a monitor displaying their camera perspective; Jeong et al, 2020), or an active role in the game (e.g., giving them essential information that the HMD player requires, thus enforcing communication; Liszio and Masuch, 2016;Smilovitch and Lachman, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These game designs can leverage the benefits of multiplayer game experiences (e.g., supporting social connectedness; Woods, 2009;Vella et al, 2019) without requiring additional HMDs. Examples include giving bystanders insight into the virtual environments (VEs) inhabited by the HMD player (e.g., via a monitor displaying their camera perspective; Jeong et al, 2020), or an active role in the game (e.g., giving them essential information that the HMD player requires, thus enforcing communication; Liszio and Masuch, 2016;Smilovitch and Lachman, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, visual and perspective information is also an important factor affecting realism. In previous studies [ 5 , 46 ], it was shown that using both first- and third-person viewpoints can significantly improve the realism and presence experienced by non-HMD users. In our system, we ensured that in addition to a first-person viewpoint, non-HMD users were also provided with a third-person viewpoint, enabling them to grasp their own position in the VE and the distance from HMD users.…”
Section: Experiments and Analysis Of Resultsmentioning
confidence: 99%
“…Setups with various levels of asymmetry differently influence the capability of users to complete tasks in a VE, thereby affecting presence and immersion. The authors of [ 5 ] proposed an asymmetric user interface to enhance the interaction between non-HMD and HMD users and to provide non-HMD users with first- and third-person perspectives to enhance user immersion. ShareVR’s research [ 1 ] explored the effectiveness of co-located asymmetric interaction between HMD and non-HMD users and used a tracked display and floor projection to visualize the virtual space for the non-HMD users, thereby increasing their immersion and enjoyment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzer olarak, Schulz, Alexandrovsky, Putze, Malaka, ve Schöning 2019 | 2020; 18 (4); Beşerî Bilimler -İktisadi İdari Bilimler Ortak Sayısı olumlu olarak etkilendiği görülmüştür (Schulz ve diğerleri, 2019). Son dönemlerde gerçekleştirilen çalışmalardan bir diğerinde Jeong, Kim, Kim, Lee, ve Kim (2020) sanal gerçeklik ortamındaki el kontrollerinin arayüz tasarımı için asimetrik bir yaklaşım izlemişlerdir. Geliştirdikleri yeni ara yüz tasarımı ile hem başa takılan görüntüleyiciler ile gerçekleştirilen hem de sadece el kontrolcüleri ile gerçekleştirilen sanal gerçeklik uygulamalarında yaşanan bulunma hissi düzeyinin arttığı tespit edilmiştir.…”
Section: Bulunma Hissi üZerine Teknik İncelemelerunclassified